2009
DOI: 10.1097/id.0b013e31818c5bd8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Titanium Surfaces in Cultures of Neonatal Rat Calvarial Osteoblast-Like Cells: An Immunohistochemical Study

Abstract: Implant surface characteristics may modulate the biological response of osteoblast-like cells depending on the manufacturing techniques and cell culturing procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This cell morphology on the surface of SLA was consistent with that observed by Aybar et al 19. In the SEM images of the SLActive group at a high cell count, few squamous cells were seen.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This cell morphology on the surface of SLA was consistent with that observed by Aybar et al 19. In the SEM images of the SLActive group at a high cell count, few squamous cells were seen.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the high cell count after 72 h despite a decrease in DNA activity suggested that rapid cell proliferation occurred in the early phase. Aybar et al 19 reached the same conclusion.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation